Pathogen- and plant-derived peptides trigger plant immunity - Yamaguchi, Koji; Kawasaki, Tsutomu (Peptides (New York, N.Y. : 1980), 2021)
•Plants recognize conserved peptides derived from pathogens by pattern recognition receptors (PRRs).•Various types of plant-derived peptides are recognized by PRRs.•Perception of peptides by PRRs involves dynamic association with co-receptors.•Peptide perception by PRRs rapidly activates immune signaling cascades. Plants are constantly exposed to pathogens in their immediate environment. Plants sense the invasion of pathogens by recognizing the components including peptide fragments derived from pathogens, known as pathogen-associated molecular patterns (PAMPs). Plants also produce immunogenic peptides called phytocytokines that regulate immune responses. These molecules are recognized by pattern recognition receptors (PRRs) at plasma membrane. Activated PRRs induce a variety of immune responses including production of reactive oxygen species (ROS), induction of Ca2+ influx and activation of mitogen activated protein kinases (MAPKs). Pattern-triggered immunity (PTI) wards off microbes and pests. In this review, we summarize recent our advances in understanding how the peptide fragments are generated and perceived by plant PRRs at cell surface, and the activated PRRs transduce the downstream immune signaling.